Exacerbating patellofemoral pain alters trunk and lower limb coordination patterns and hip-knee mechanics - Briani, Ronaldo Valdir [UNESP]; Cannon, Jordan; Ducatti, Matheus Henrique Maiolini [UNESP]; Priore, Liliam Barbuglio Del [UNESP]; Botta, Ana Flavia Balotari [UNESP]; Magalhães, Fernando Henrique [UNESP]; Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2022)
The exacerbation of patellofemoral pain (PFP) may lead to compensatory trunk and lower limb movement patterns in order to minimize patellofemoral joint loading. However, joint kinematics are often analysed in isolation, which limits the understanding of how the underlying segments were coordinated to produce limb postures and distribute load across the limb. In this study we used a dynamical systems approach to investigate how women with PFP coordinate trunk, hip, and knee motion and distribute hip-knee moment demands following symptom exacerbation. Coordination patterns and coordination variability of the trunk, hip, and knee from 61 women with PFP were obtained during stair descent, ascent, and step down tasks, before and after a pain exacerbation protocol. Hip-knee extensor moment impulse ratio was also calculated. Following the exacerbation of PFP, women utilized knee dominant coordination patterns less often (p = 0.039–0.027; d = 0.51–0.53), while coordination patterns with the trunk leaning forward were utilized more during stair negotiation (p = 0.043-<0.001; d = 0.52–0.96). Although no significant differences in hip-knee coordination patterns were found, there was an increase in the hip-knee impulse ratio during stair negotiation (p = 0.014-<0.001; d = 0.27–0.36). These findings seem to display a movement strategy utilized by women with PFP in order to distribute more load to the hip joint and less to the knee joint, possibly in an attempt to avoid/manage pain.
Keywords: Dynamical systems approach; Knee pain; Modified vector coding; Stair negotiation; Trunk flexion